Regulation of Medical Waste Management Based on Green Legislation in the Era of Omnibus Law - Eko Nurmardiansyah; Endang Wahyati Y. (Soepra Jurnal Hukum Kesehatan, 2022)
Abstracts: Medical waste management must be based on laws and regulations related to environmental protection and management, of course, as well as laws and regulations in the health sector because medical waste is leftover from the business and / or activities of health service facilities. The management of medical waste as part of the protection and management of the environment must certainly be in accordance with the direction of legal policies set by the state or government to achieve the goals and objectives of environmental protection and management, so that it can be understood, implemented, and enforced the principles or principles and legal norms in it comprehensively in accordance with the politics of environmental law. The implementation of national development must be pro-environment or protect the environment in accordance with the principles of sustainable development that ensure the survival and maintenance of the carrying capacity of the environment for the lives of the next generations. Keywords: · Medical Waste ·  Green Constitution · Green Legislation · Principle.  Abstrak: Pengelolaan limbah medis wajib mendasarkan pada peraturan perundang-undangan yang terkait dengan PPLH dan tentunya juga peraturan perundang-undangan di bidang kesehatan karena limbah medis merupakan sisa dari usaha dan/atau kegiatan dari Fasyankes. Pengelolaan limbah medis sebagai bagian dari PPLH tentu harus sesuai dengan arah kebijakan hukum yang ditetapkan oleh negara atau pemerintah untuk mencapai tujuan dan sasaran dari PPLH, agar dapat dipahami, dilaksanakan, dan ditegakkannya prinsip-prinsip atau asas-asas dan norma hukum yang ada di dalamnya secara komprehensif sesuai dengan politik hukum lingkungan. Penyelenggaraan pembangunan nasional haruslah bersifat prolingkungan atau melindungi lingkungan hidup sesuai dengan prinsip pembangunan berkelanjutan (sustainable development) yang menjamin kelangsungan hidup dan terpeliharanya daya dukung lingkungan untuk kehidupan generasi-generasi selanjutnya.Kata Kunci: · Limbah Medis · Konstitusi Hijau · Peraturan Perundang-undangan Berbasis Lingkungan · Asas.